PENGARUH KOMPRES HANGAT JAHE MERAH TERHADAP NYERI ASAM URAT PADA LANSIA DI RW 004 KAMPUNG RAWA BOKOR KOTA TANGERANG TAHUN 2021 - Darmawansyah, Saputra; Rochmani, Siti (Nusantara Hasana Journal, 2022)
Gouty arthritis is characterized by high levels of uric acid in the blood and repeated attacks of acute pain in the joints. One of the non-pharmacological pain management is to apply a warm red ginger compress. Gout (Gout Arthritis) is more common in men, especially those over the age of 30 because they generally have high uric acid levels in their blood. This study was conducted with the aim of knowing the effect of red ginger warm compresses on gout pain in the elderly in the village of Rawa Bokor, Tangerang City in 2021. The design of this study used a Quasy-Experimental Design with a One Group Pretest-Posttest Design, the data were collected by observation and measurement of pain scale, the research used in this study is descriptive correlation. Based on the results, it is known that the Z value in the pre-post variable, the level of uric acid joint pain is - 16,248b with a p value of Asymp. Sig. (2-tailed) of .000 < 0.05, it can be concluded "There is an effect of giving warm red ginger compresses on reducing pain scale in the elderly with gout in Rw 004, Rawa Bokor Village, Tangerang City". The conclusion of this study states that there is an effect of giving red ginger warm compresses to reducing gout pain in the elderly in Rw 004, Rawa Bokor Village, Tangerang City.